Analisis fenomena dan intervensi gangguan bermain game daring internet gaming disorder pada siswa - Annisaislami Khairati; Ifdil Ifdil; Rima Pratiwi Fadli; Nur Adila Wafiqoh Zulfi (Jurnal Konseling dan Pendidikan, 2025)
Internet Gaming Disorder (IGD) has emerged as a significant mental health concern among adolescent students, with prevalence rates varying from 0.7% to 27.5% globally.  This study aimed to comprehend-sively describe IGD tendencies among students in urban public schools, identify the most prominent IGD dimensions, and formulate evidence-based implications for guidance and counseling interventions. A quantitative descriptive study was conducted involving 350 high school students from three urban public schools in West Sumatra, selected through simple random sampling. Data were collected using a standardized six-dimension IGD questionnaire measuring Salience, Tolerance, Mood Modification, Withdrawal, Relapse, and Conflict.The findings revealed that 45.7% of students exhibited moderate IGD tendencies, with only 5.7% in the very low category. The most prominent dimensions were Tolerance (75.0% in moderate-to-high categories) and Relapse (49.0% in moderate category), reflecting significant difficulties in controlling gaming duration and strong urges to resume gaming after cessation attempts. Maternal employment status (65.7% working mothers) potentially contributed to reduced parental supervision.IGD tendencies among urban public school students represent a significant risk requiring urgent intervention. School counseling services must implement comprehensive prevention programs incorporating self-control enhancement, family involvement, and evidence-based group counseling approaches.